THE EFFECT OF THEMATIC PATTERNING TECHNIQUE ON WRITING ACHIEVEMENT AND ITS RELATIONSHIP TO STUDENTS’ ACHIEVEMENT MOTIVATION - krisna, adi (Jurnal Pendidikan dan Pengajaran, 2017)
ABSTRACT             This study aimed at investigating the effect of thematic patterning technique and achievement motivation on students’ writing achievement. The subjects were the second semester students of English Education Department in the academic year 2015/2016. The II B class was assigned as the experimental group and II D class as the control group. The experimental group was taught by using thematic patterning technique and the control group by using conventional technique. The instruments were achievement motivation questionnaire and writing achievement test. The findings showed there was a significant difference in writing achievement between the students taught by using thematic patterning technique and those taught by using conventional technique. The mean score of students taught by using thematic patterning technique was higher than the students taught by using conventional technique; there was interaction between of thematic patterning technique and the achievement motivation in learning English on students’ writing achievement. Keywords: thematic patterning technique, achievement motivation, students’ writing achievement